Echocardiographic measurements of left ventricular end-diastolic diameter and interventricular septal diameter in collegiate football athletes at preparticipation evaluation referenced to body surface area - Katherine M Edenfield; Fred Reifsteck; Stephen Carek; Kimberly G Harmon; Breton M Asken (BMJ Open Sport & Exercise Medicine)
Background Are borderline echocardiogram structural measurements due to physiological adaptation or pathology in college football players? The normal reference data are very limited in this population. We report left ventricular end-diastolic diameter (LVEDD) and interventricular septal diameter (IVSD) echocardiogram findings in college football athletes.Methods and results A retrospective cohort review of preparticipation examination transthoracic echocardiogram measurements of LVEDD and IVSD from 375 American collegiate football athletes cleared for participation from the University of Florida in 2012–2017 and University of Georgia in 2010–2015 was performed.LVEDD and IVSD were analysed by field position (lineman, n=137; non-lineman, n=238), race (black, n=216; white, n=158) and body surface area (BSA) for associations. Values were compared with non-athlete norms, and collegiate football athlete-specific reference norm tables were created.Twenty-one (5.6%) athletes had LVEDD and 116 (31%) had IVSD measurements above the reference normal non-athlete values. Univariate analyses indicated that the lineman position and increasing BSA were associated with larger values for LVEDD and IVSD. Black race was associated with larger IVSD values, and white race was associated with larger LVEDD values. Player position correlated strongly with BSA (r>0.7); we created normal reference tables for LVEDD and IVSD, stratified by BSA group classification (low, average and high BSA). Proposed clinical cut-offs for normal and abnormal values are reported for raw echocardiograph metrics and BSA-indexed scores.Conclusions A significant number of collegiate football athletes had LVEDD and IVSD values above non-athlete norms. BSA-specific normal values help clinicians interpret results for football athletes.